THE DOCTRINE OF PIERCING THE CORPORATE REVIEW IN THE COURT DECISION NO. 656/PDT.G/2015/PN.MDN - Abdul Rahman Praja Negara (Indonesia Private Law Review, 2021)
Limited Liability Company (Ltd.) or Perseroan Terbatas (PT) is a legal entity in Indonesia that constitutes a capital alliance formed by an agreement that features a limited liability principle. Limited liability is a principle that limits the responsibility of shareholders to the risk of the Company. However, the principle of limited liability is frequently misapplied, as shareholders look for ways to protect themselves from the risk of more significant losses, to take advantage of all company profits for personal gain. Shareholders who abuse the principle of limited liability for personal gain, on the other hand, will be subject to the Piercing the Corporate Veil doctrine. This doctrine imposes the transfer of liability for personal losses to shareholders who cause harm to the company in bad faith. Based on this understanding, this paper seeks to comprehend the application of the Piercing the Corporate Veil doctrine by analyzing Medan District Court Decision Number: 656/Pdt.G/2015/PN.Mdn. The research method used in this study was normative legal research reviewed with a statute approach and a conceptual approach. The conclusion drawn from the problem is as follows: the regulation regarding the Piercing the Corporate Veil doctrine is borne not only by shareholders but also by the Board of Directors and the Board of Commissioners who fail to implement the principles of fiduciary duty of skill and care. Furthermore, in the case of 656/Pdt.G/2015/PN.Mdn, the judge considered the provisions of Article 3 paragraph (2) of the UUPT in implementing the Piercing the Corporate Veil Doctrine by punishing the Defendants jointly and severally to indemnify the Plaintiff.